Creative collaboration - John-Steiner, Vera (Oxford University Press, 2000)
Rodin's sculpture "The Thinker" dominates our collective imagination as the purest representation of human inquiry--the lone, stoic thinker.But while the Western belief in individualism romanticizes this perception of the solitary creative process, the reality is that scientific and artistic forms emerge from the joint thinking, passionate.